Plant-based veterinary practices in Peru: a review of traditional ethnoveterinary knowledge and phytochemical components. - Silva, W. (2024)
Background: For millennia, medicinal plants have been employed in ethnoveterinary practices to cure and avert diseases in domesticated animals, particularly livestock. Ethnoveterinary medicine studies traditional beliefs, knowledge and practices to maintain the health and well-being of animals, using mainly plants, minerals, animals and magical-religious or spiritual elements in prevention, diagnosis, treatment and healing. In Peru, the trend of urban migration has led to a decline in traditional knowledge regarding the use of medicinal plants in veterinary treatment. This study aims to pinpoint the medicinal plants traditionally employed in Peru and to identify their phytochemical makeup. Methods: A comprehensive literature review was conducted using various online databases, including Google Scholar, Web of Science, ResearchGate, Scopus, ScienceDirect, university databases and other related publications. Results: In total, 13 studies were found that refer to the use of medicinal plants in ethnoveterinary medicine in Peru. The studies recorded a total of 189 plant species from 61 families, used in treating a variety of diseases in Peruvian domestic animals. In ethnoveterinary medicine, a total of 58 conditions were identified, primarily in livestock and alpacas. The most frequently observed conditions were diarrhea (23%), fever (13%), worm infestation (10%), pneumonia (8%), and mastitis (7%). Among the 189 species used in Peruvian ethnoveterinary medicine, 69% have studies on their phytochemical components listed in the databases. The most important phytochemical compounds found were simple and complex phenolic compounds, essential oils, including simple and complex terpenes. Other less frequent were phytosterols, alkaloids, glycosides, quinones and peptides. Conclusions: Studies on ethnoveterinary medicine in Peru document 181 plant species used in the treatment of ailments in cattle, llamas and alpacas, mainly. The most common diseases include diarrhea, fever and mastitis. Approximately 69% of these plants have been studied for their phytochemical content, were found mainly polyphenols, oils, alkaloids, quinones and peptides. While for the rest of the plants there is no record of their components, which represents an opportunity for future research.